ARTIKEL REVIEW: Penggunaan Obat Herbal Dalam Upaya Swamedikasi atau Pengobatan Sendiri Pada Penyakit Batuk Dan Flu - Suardika, I Wayan Gede; Amesti Dewi , Ni Made Wahyuni; Megawati, Fitria (Usadha, 2023)
Self-medication is a treatment that is carried out alone or independently with the aim of preventing or treating a disease. Diseases that are usually carried out by self-medication are coughs and flu. This article aims to look at the potential of herbal medicines in Indonesia as self-medication in the treatment of coughs and flu. The important value in this review article is the use of herbal plants in self-medication. The type of research method used in this review article is using review article studies, by collecting data derived from articles in journal form on the topic of using herbal medicines in self-medication efforts or self-medication for coughs and flu in the last 10 years. Retrieval of articles with a range of the last 10 years is still considered relevant and well used. Herbal medicine that has been widely used in the last 10 years is ginger (Zingiber officinale). Ginger is widely used because it has been proven empirically.